PSD-EEGRepNet: A CNN Architecture with Multibranch RepBlocks for Power Spectral Density-Based Motor Imagery EEG Classification in BCI - Kantham Thangthong; Fawad Asadi; S. Tungjitkusolmun (My University, 2025)
Motor Imagery (MI) based Brain-Computer Interfaces (BCIs) utilizing electroencephalography (EEG) offer significant potential, yet progress can be hindered by the computational demands of deep learning classifiers. This study introduces and evaluates a novel lightweight, multi-branch Convolutional Neural Network (CNN), inspired by efficient design principles, specifically for classifying MI tasks from Power Spectral Density (PSD) EEG features. Our objective was to achieve strong classification performance coupled with favorable development phase computational characteristics. Evaluated on 10 subjects from a public PhysioNet dataset using 5-fold crossvalidation and two data overlap conditions (80%, 90%), the proposed model $(\sim 6.32 \mathrm{M}$ parameters, $\sim 20$ MFLOPs) demonstrated high mean classification accuracies (80.38% for 80% overlap, 85.69% for 90% overlap) and efficient training times (avg. 8.8s and 20.4s per fold, respectively). While performance scaled positively with data augmentation, intersubject variability was noted. We conclude that the proposed architecture effectively balances high accuracy with significant offline computational efficiency offering a valuable tool for BCI research and a promising foundation for developing practical MIBCI systems.
Keywords: EEG and Brain-Computer Interfaces; Functional Brain Connectivity Studies; Neuroscience and Neural Engineering